Implementation of Good Governance at The Secretariat of The Regional House of Representatives (DPRD) of Bogor City - Sultoni, Muhammad Rafli; Seran, Gotfridus Goris; Ramdani, Faisal Tri (Public Policy Journal, 2025)
This study aims to examine the implementation of good governance in the Secretariat of the Bogor City Regional House of Representatives (DPRD). It employs a descriptive quantitative research method, with data collected through questionnaires, observations, and interviews. The number of respondents in this study is 56. The analytical technique used is the Weighted Mean Score (WMS). The results of this study indicate that the implementation of good governance in the Secretariat of the Bogor City DPRD has generally been well-executed. This is evidenced by the high average scores across the three dimensions used in the study—transparency, accountability, and responsiveness—which obtained an overall average score of 4.20, falling under the "Good" category.